2021
DOI: 10.1186/s12935-021-01892-1
|View full text |Cite
|
Sign up to set email alerts
|

An updated review of mechanistic potentials of melatonin against cancer: pivotal roles in angiogenesis, apoptosis, autophagy, endoplasmic reticulum stress and oxidative stress

Abstract: Cancers are serious life-threatening diseases which annually are responsible for millions of deaths across the world. Despite many developments in therapeutic approaches for affected individuals, the rate of morbidity and mortality is high. The survival rate and life quality of cancer patients is still low. In addition, the poor prognosis of patients and side effects of the present treatments underscores that finding novel and effective complementary and alternative therapies is a critical issue. Melatonin is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 202 publications
1
30
1
5
Order By: Relevance
“…MLT is an active hormone secreted by the conarium and has antioxidant stress and anti-inflammatory functions ( Reiter et al, 2014 ; Reiter et al, 2017 ; Amaral and Cipolla-Neto 2018 ; Cipolla-Neto and Amaral 2018 ; Hardeland 2018 ). Based on previous research, MLT protects against ischemia-reperfusion and cancer, which are closely related to improving angiogenesis and suppressing apoptosis ( Yeung et al, 2015 ; Sun et al, 2016 ; Gou et al, 2020 ; Mehrzadi et al, 2021 ). However, it is unclear what effect MLT has on multi-territory perforator flaps.…”
Section: Discussionmentioning
confidence: 99%
“…MLT is an active hormone secreted by the conarium and has antioxidant stress and anti-inflammatory functions ( Reiter et al, 2014 ; Reiter et al, 2017 ; Amaral and Cipolla-Neto 2018 ; Cipolla-Neto and Amaral 2018 ; Hardeland 2018 ). Based on previous research, MLT protects against ischemia-reperfusion and cancer, which are closely related to improving angiogenesis and suppressing apoptosis ( Yeung et al, 2015 ; Sun et al, 2016 ; Gou et al, 2020 ; Mehrzadi et al, 2021 ). However, it is unclear what effect MLT has on multi-territory perforator flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been proven as an ideal anticancer agent in various cancers 29‐32 . Studying melatonergic regulators in cancer is necessary to understand tumorigenesis and to explore potential targets for clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin receptor suppresses ER-α-mediated transcriptional activity in ER-α-positive breast tumor cells. The arrest of cell cycle and the cell proliferation are mediated by the inhibitory actions on Ca 2+ signaling and CaM expression [25], stimulation of p53 expression [45], and p21-gene transcription (Figure 2) [46]. It was reported that blocking of MT1/MT2 receptors in MCF-7 cells showed impaired p53-mediated repairing of DNA damage [47].…”
Section: Anti-proliferative Effects Of Melatonin On Breast Cancer Cellsmentioning
confidence: 97%